38.2k views
2 votes
Can someone help me ? i have no clue how to figure this out

Can someone help me ? i have no clue how to figure this out-example-1

2 Answers

1 vote


\cos \: t ( \sec \: t - \cos \: t) = \sin^(2)t \\ \\ 1. \: 1 - ( \cos \: t )/( \sec \: t ) = \sin^(2) t \\ 2. \: 1 - \cos \: t \cos \: t = \sin^(2) t \\ 3. \: 1 - \cos^(2) t = \sin^(2) t \\ 4. \: 1 - \cos^(2) t - \sin^(2) t = 0 \\ 5. \: 1 - 1 = 0 \\ 6. \: 0 = 0 \\ 7. \: infinitely \: many \: solutions

User Sever
by
6.1k points
4 votes


\cos t (\sec t - \cos t) = \sin^2 t


\cos t ((1)/(\cos t) - \cos t) = \sin^2 t


(\cos t)/(\cos t) - \cos^2 t = \sin^2 t


1 - \cos^2 t = \sin^2 t

Use the identity:
\sin^2 t + \cos^2 t = 1 and solve for
\sin^2 t. You get:
\sin^2 t = 1 - \cos^2 t

Do the substitution on the left side to get:


\sin^2 t = \sin ^2 t

User Abdulaziz Noor
by
5.3k points